DIPERLUKAN PENDEKATAN KEBIJAKAN ADAPTIF UNTUK PENGUATAN MODAL UMKM DI KABUPATEN SLEMAN - Suci Iriani Sinuraya; Muhadjir Darwin; Yeremias T Keban; Sukamdi Sukamdi (Universitas Gadjah Mada, 2018)
This paper examines implementation of micro credit policies of non-bankable Small Medium Enterpries (SME’s) in Sleman Regency in 1999-2000. It explores the impact of dynamic policy changing on rates, collateral, and legal aspects as the requirements to access micro credit program. This study employed a qualitative case study, to describe backgrounds, effectiveness, and policy impacts. The data collecting methods included interviews, obeservations, and focus group discussion (FGD). The participants have been set up. Two category of respondent: decision makers and street-level bureaucrats and (candidate) beneficiary program. The research was conducted in October 2016–December 2017. The results show that policy changing on rate, collateral and legality created impacts on the SME’s interest in accessing the credit. The participants of non-bankable SMEs showed that their interest decreased when there were further requirement to attach credit collateral and legal aspects. Therefore, the bankable SMEs become the groups which leverage the micro credit program. On the contrary, the program did not work effectively to entrepreneurs, the non bankable SMEs as the prime targetted group in Sleman. Meanwhile, the appearence of cooperative as an executing body, to which the nonbankable SMSEs,looking for capital. So, the capital from UPT PDPM should through two steps to to reach the non bankable SMEs. The Recommendation is Sleman Regency using adaptive policy to show their affirmation to non bankable SME’s facing the dynamic situation nowadays.